Coordination of cage compounds by Cu(I) nacnac compounds. (1st September 2022) - Haimerl, Maria; Spitzer, Fabian; Timoshkin, Alexey Y.; Seidl, Michael; Scheer, Manfred
Graphical abstract: The reactions of [nacnacCu(MeCN)] with P 4, As4, AsP3, Sered, P4 S3 and As4 S3, respectively, lead to the mono- and dinuclear copper complexes containing intact E4 or E4 S3 (E = P, As) units. The integrity of the copper coordinated bonds was elucidated by DFT calculations. Abstract: The nacnac Cu(I) compound [L 1 Cu(MeCN)] (L 1 = [N(C6 H3 Me2 -2, 6)C(Me)2 CH] − ) was reacted with E4 ( P 4, As4 and AsP3 ) yielding the homobimetallic complexes [(L 1 Cu)2 (η 2:2 -E4 )] (E4 = P 4 (1a ), As4 (1b ), AsP3 (1c )) and the mononuclear complexes [L 1 Cu(η 2 -E4 )] (E4 = P 4 (2a ), As4 (2b ), AsP3 (2c )), revealing neutral, intact side-on coordinated E4 units. Furthermore, the reaction of [L 1 Cu(MeCN)] with Sered and E4 S3 (E = P, As) afforded [(LCu)2 (μ, η 2:2 Se2 )] (L 1 = 3a, L 3 = 3b ) and [(L 3 Cu)2 (E4 S3 )] (E = P (4 ), As (5 )). They represent rare examples of complexes of group 11 metals with polypnictogen, chalcogen and mixed E15/Q16 compounds.